Simple series Relation

Algebra Level 3

If x = 1 1 2 + 1 3 2 + 1 5 2 . . . . . x\quad = \frac { 1 }{ 1^ 2 } +\frac { 1 }{ 3^ 2 } +\frac { 1 }{ 5^ 2 } ..... ,,,,, y = 1 1 2 + 3 2 2 + 1 3 2 + 3 4 2 + . . . . y\quad =\quad \frac { 1 }{ 1^ 2 } +\frac { 3 }{ 2^ 2 } +\frac { 1 }{ 3^ 2 } +\frac { 3 }{ 4^ 2 } +.... , z = 1 1 2 1 2 2 + 1 3 2 1 4 2 + . . . . z\quad =\quad \frac { 1 }{ 1^ 2 } -\frac { 1 }{ 2^ 2 } +\frac { 1 }{ 3^ 2 } -\frac { 1 }{ 4^ 2 } +.... , then which of the following is true ?

y 6 , x 3 , z \dfrac{y}{6}, \dfrac{x}{3}, z are in A.P. 6 y , 3 x , 2 z 6y,3x,2z are in A.P. y 6 , x 3 , z 2 \dfrac{y}{6}, \dfrac{x}{3}, \dfrac{z}{2} are in A.P. x , y , z x, y, z are in A.P.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Ronak Agarwal
Jul 24, 2014

T a k e a = n = 1 1 ( 2 n 1 ) 2 a n d b = n = 1 1 ( 2 n ) 2 . S o w e h a v e x = a y = a + 3 b z = a b H e n c e w e h a v e y 6 + z 2 = a + 3 b 6 + a b 2 = 2 a 3 2 ( x 3 ) . y / 6 , x / 3 , z / 2 a r e i n A P Take\quad a=\sum _{ n=1 }^{ \infty }{ \frac { 1 }{ { (2n-1) }^{ 2 } } } \quad and\quad b=\sum _{ n=1 }^{ \infty }{ \frac { 1 }{ { (2n })^{ 2 } } } .\\ So\quad we\quad have\quad x=a\quad \quad y=a+3b\quad \quad z=a-b\\ Hence\quad we\quad have\quad \frac { y }{ 6 } +\frac { z }{ 2 } =\frac { a+3b }{ 6 } +\frac { a-b }{ 2 } =\frac { 2a }{ 3 } 2(\frac { x }{ 3 } ).\\ \Rightarrow y/6,x/3,z/2\quad are\quad in\quad AP

You forgot the last equal sign. That caused me confusion at first. Very nice solution though! I don't think it can get any easier.

James Wilson - 3 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...